2019
DOI: 10.1016/j.bpj.2018.11.3141
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-Conjugated Rigidochromic Probe Discloses Membrane Alteration in Model Cells of Krabbe Disease

Abstract: The plasma membrane of cells has a complex architecture based on the bidimensional liquid-crystalline bilayer arrangement of phospho-and sphingolipids, which in turn embeds several proteins and is connected to the cytoskeleton. Several studies highlight the spatial membrane organization into more ordered (L o or lipid raft) and more disordered (L d ) domains. We here report on a fluorescent analog of the green fluorescent protein chromophore that, when conjugated to a phospholipid, enables the quantification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…In the present study, we have shown that miR-219 reduced psychosine accumulation in developing twitcher OLs (Figure 5). Recent studies have shown that psychosine preferentially accumulates in membrane microdomains in the brain of KD patients and twitcher mice, leading to the disruption of lipid rafts that play a crucial role in membrane trafficking and cell signaling (44)(45)(46)(47). In addition, it has been known that psychosine mediates apoptotic cell death via caspase-3 activation in various cell types (45,(48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we have shown that miR-219 reduced psychosine accumulation in developing twitcher OLs (Figure 5). Recent studies have shown that psychosine preferentially accumulates in membrane microdomains in the brain of KD patients and twitcher mice, leading to the disruption of lipid rafts that play a crucial role in membrane trafficking and cell signaling (44)(45)(46)(47). In addition, it has been known that psychosine mediates apoptotic cell death via caspase-3 activation in various cell types (45,(48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%
“… [70] Although not covered here in detail, other rotor dyes have also been used to investigate the microviscosity of lipid membranes and intracellular compartments; through intensity, ratiometric, or lifetime‐based measurements. These include merocyanine, [112] anthracene, [113] triphenylamine, [114] juliodine,[ 32 , 33 ] porphyrin,[ 45a , 46b ] pyrrolic compounds, [115] GFP, [87a] or indocarbocyanine nanoparticle [116] —based molecular rotors.…”
Section: Molecular Rotors For Biological Imagingmentioning
confidence: 99%
“…The main advantages of phasor analysis are that it provides a visual distribution of the molecular species by clustering pixels with similar decays, it allows for color mapping of the pixels of the FLIM images, and it is linear in terms of non-interacting molecular species. (15,16,21,22) Phasor analysis of FLIM data is increasingly used in several fields of biomedical research (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) and is particularly useful for metabolic imaging with the endogenous biomarkers NAD(P)H and FAD to map their complex autofluorescence distributions in live tissues in the context of different physiopathological processes. (5,16, .…”
Section: Introductionmentioning
confidence: 99%